Severe Abdominal Wall Infection After Subcostal Transversus Abdominis Plane Block: A Case Report. Issue 10 (October 2021) - Hang, Dustin; Weich, Dean; Anderson, Christopher; Dolinski, Sylvia Yvonne
Abstract : Transversus abdominis plane (TAP) blocks are increasingly used for perioperative analgesia in patients undergoing abdominal surgeries. TAP blocks are easy to perform, reliably effective, and have an excellent safety profile. Nevertheless, we report a patient who underwent an open cholecystectomy and right hemicolectomy where a subcostal TAP block possibly contributed to an unusual abdominal wall abscess that lead to a prolonged and complicated postoperative course.